Efektivitas Model Pembelajaran Berbasis Inkuiri dalam Meningkatkan Pemahaman Konsep Biologi - Damar Wisanggeni; Fikri Handoko Pranata (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Inquiry-based learning is a pedagogical approach that encourages students to actively construct their knowledge through exploration and questioning. This study aims to analyze the effectiveness of the inquiry-based learning model in improving students' conceptual understanding of biology. The research employs a quasi-experimental design with a pre-test and post-test control group. Data were collected from high school students and analyzed using statistical tests to compare learning outcomes between the experimental and control groups. The findings indicate that students who learned through inquiry-based methods demonstrated significantly higher conceptual understanding than those in traditional learning settings. These results suggest that the inquiry-based learning model can enhance students' critical thinking skills and conceptual mastery, making it a valuable approach for biology education. The study's implications highlight the need for integrating inquiry-based learning in science curricula to foster deeper understanding and engagement among students.